Legal framework on the protection, health and welfare of animals used for experimental and educational purposes - KOSTOMITSOPOULOS (Ν. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ) N.; ARVANITI (Α. ΑΡΒΑΝΙΤΗ) A.; DILE (Χ. ΔΗΛΕ) X.; PAPADOPOULOS (Η. ΠΑΠΑΔΟΠΟΥΛΟΣ) H.; PAPATSIROS (Β.Γ. ΠΑΠΑΤΣΙΡΟΣ) V. G.; KYRIAKIS (ΚΥΡΙΑΚΗΣ Σ.Κ.) S. (Journal of the Hellenic Veterinary Medical Society, 2017)
The use of animals for experimental and educational purposes is regulated by a national legal framework in accordance to the European Directive 86/609 and the European Convention ETS 123 of the Council of Europe. Main issues regulated by the above legislation are the license procedure for the use of laboratory animals, the registration of breeding, supplying and experimental establishments, the implementation of guidelines for the appropriate care and use of the animals, the collection of statistical information and the promotion of alternative to animal experimentation methods. The veterinarian plays an important role for the protection, the health and the welfare of laboratory animals. This role is well defined within the existing legislation. The supervision of the veterinarian guarantees also the quality of the obtained results from animal experimentations. After twenty years, the scientific community and the animal welfare associations recognized the need for the revision of the existing European legal framework under the new obtained scientific knowledge. The Council of Europe has recently revised the Appendix A of the European Convention ETS 123 and the Commission of the European Union initiated the process for the revision of the European Directive 86/609. Ethical evaluation, authorization procedures and registration of establishments are, also, expected to be revised.